EFEKTIFITAS PENDIDIDIKAN KESEHATAN MENGGUNAKAN AUDIO VISUAL TERHADAP PENGETAHUAN IBU TENTANG GIZI SEIMBANG PADA BALITA DI POSYANDU CEMARA KARYA INDAH PUSKESMAS PANTAI CERMIN - Vivi Silviani; Lisviarose Lisviarose; Rizka Mardiya; Meirita Herawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Balanced nutrition is an important factor in the growth and development of toddlers. Low maternal knowledge about balanced nutrition can affect the selection and preparation of food that is not appropriate for children. Audiovisual media is considered an effective health education method because it combines audio and visual elements, making information easier to understand and remember. This study aimed to determine the effectiveness of health education using audiovisual media on mothers’ knowledge of balanced nutrition for toddlers at Posyandu Cemara Karya Indah, in the working area of UPT Puskesmas Pantai Cermin. This research was quantitative with a quasi-experimental design and a pretest-posttest with control group approach. The sample consisted of 46 respondents, divided into intervention and control groups, with 23 people in each group, selected using purposive sampling. The instrument used was a questionnaire on knowledge about balanced nutrition. Data analysis was carried out using the Shapiro-Wilk normality test and the mann-whitney with a significance level of 0.05. The results showed that the average knowledge score of the control group was 62,22, while the intervention group, which was given health education using audiovisual media, had an average score of 82.61. The mean difference between the two groups was 20.39 points. Statistical testing showed a p-value = 0.001 (p 0.05), indicating a significant difference between the two groups. In conclusion, health education using audiovisual media is effective in increasing mothers’ knowledge about balanced nutrition for toddlers. It is recommended that health centers integrate audiovisual media into routine health education activities, and that future researchers conduct long-term measurements to assess behavioral change.Keywords: Balanced nutrition, health education, audiovisual media, toddlers